2021
DOI: 10.3389/fnins.2021.689601
|View full text |Cite
|
Sign up to set email alerts
|

Reactive, Adult Neurogenesis From Increased Neural Progenitor Cell Proliferation Following Alcohol Dependence in Female Rats

Abstract: Hippocampal neurodegeneration is a consequence of excessive alcohol drinking in alcohol use disorders (AUDs), however, recent studies suggest that females may be more susceptible to alcohol-induced brain damage. Adult hippocampal neurogenesis is now well accepted to contribute to hippocampal integrity and is known to be affected by alcohol in humans as well as in animal models of AUDs. In male rats, a reactive increase in adult hippocampal neurogenesis has been observed during abstinence from alcohol dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…In agreement with our results, increased dendritic spine density and neurogenesis in the dentate gyrus and enhancement of hippocampal neuronal arborization were found in alcohol-exposed male rats [ 23 , 46 , 47 ]. Since BDNF plays a potential role in promoting cell proliferation and neurogenesis, these reactive responses are thought to contribute to repair and recovery of the hippocampus of males that showed spatial memory impairment [ 48 , 49 ]. Thus, the upregulation of BDNF-TrkB-PLCγ1 signaling in the hippocampus of males were hypothesized to contribute to recovery after hippocampal damage induced by alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our results, increased dendritic spine density and neurogenesis in the dentate gyrus and enhancement of hippocampal neuronal arborization were found in alcohol-exposed male rats [ 23 , 46 , 47 ]. Since BDNF plays a potential role in promoting cell proliferation and neurogenesis, these reactive responses are thought to contribute to repair and recovery of the hippocampus of males that showed spatial memory impairment [ 48 , 49 ]. Thus, the upregulation of BDNF-TrkB-PLCγ1 signaling in the hippocampus of males were hypothesized to contribute to recovery after hippocampal damage induced by alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to males, females with alcohol-related cognitive impairment have a slower recovery after 6 weeks of abstinence [ 50 ]. Similarly, increased cell proliferation and immature neurons number were found in female rats on the 14th day of abstinence from alcohol [ 49 ]. These observations indicate that females may suffer from more prolonged memory impairment compared to males and had a slower recovery from alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al reported that two-month voluntary alcohol drinking stimulated neurogenesis in the DG and SVZ of male cHAP mice [ 59 ]. Recently, four-day binge drinking was shown to increase hippocampal neurogenesis in adult female Sprague-Dawley rats [ 60 ]. In the present study, although LAC tended to increase both DCX + /BrdU + and NeuN + /BrdU + cells in the DG, the increase did not reach statistically significant levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hilar ectopic DGCs form abnormal neural connections with adjacent DGCs and interfere with hippocampal neural circuits [49,63,64]. Although these cells have been mainly studied in temporal lobe epilepsy, which is characterized by recurrent seizures accompanied by temporarily increased hippocampal neurogenesis, they are also observed in patients with schizophrenia and alcoholism [65][66][67]. In traumatic brain injury, neurons formed after excessive stress such as trauma are localized ectopically to the hilus and molecular layer in the hippocampus [68,69].…”
Section: Discussionmentioning
confidence: 99%